Optimal parameters for extracting exhaust gas heat from boilers to be used by heat pump - Dubovskoy S.V.; Babin; Kobernik V.S.; Kadenskiy N.Y. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
The article deals with estimation of advisable parameters of exhaust gas heat extraction from boilers to be used by a heat pump. The existing works on the issue were analyzed to find out the secure supply of maximum exergy of extracted heat to be important.The main aim of the research is to determine the condition of maximum exergy of the heat, received by a heat exchanger-condenser at isobaric gas-steam mixture cooling at a given value of dew point deficit of cooled gases. By the example of a PTVM 100 boiler the simulation and optimization modeling of flue gases cooling process in recovery heat exchangers was carried out using the principle of heat and mass exchange similarity.The heat exchanger-condenser optimum temperature values were determined to be obviously maintained within 36°C - 41°C range, depending on the boiler load, while the temperature of cooling gases must be held within 52°C - 66°C range, in compliance with increasing dew point restrictions within 10°C - 20°C range, depending on thermal and technical features of flue pipes and stacks.The recovery coefficient of exhaust gases heat increases at the indicated cooling mode and decreases with growing flue gases dew-point deficit restrictions.The presented data allow selecting the required heat pump parameters and evaluating the effectiveness of measures aimed at heat insulation of boiler’s flue gas pipes and stacks based on their actual thermal performance.